The protective effect of inactivated Flavobacterium columnare vaccine in grass carp (Ctenopharyngodon idellus) - Guo, Wenjie; Han, Rui; Xu, Weizhen; Lu, Zijun; Li, Yanwei; Dan, Xueming; Mo, Zequan (Frontiers in Immunology, 2023)
Flavobacterium columnare, which causes columnaris disease, is responsible for significant mortality in grass carp. Vaccination is a safe and effective measure to combat this disease, and this study aimed to investigate the immune protective effects of different treatments using an inactivated F. columnare vaccine. The vaccine was prepared by inactivating the bacteria with 0.05% formaldehyde at 4℃ for 24 hours. The experiments involving grass carp were divided into two parts. In Experiment 1, the immune effects of two isolates, JX-01 (genomovar I) and MU-04 (genomovar II), were compared, along with the impact of white oil adjuvant and the number of immunizations. The results showed that when the white oil adjuvant was used as a booster, the relative percent survival (RPS) of the JW2 group and MW2 group after 8 weeks of the first immunization were 34% and 61%, respectively. In Experiment 2, only the MU-04 (genomovar II) isolate was used as an antigens with the white oil adjuvant as a booster. The effects of different doses (CFU=10 8 , 10 7 , and 10 6 bacteria/mL) on immune responses were compared, and the RPS values in the MW6, MW7, and MW8 groups after 4 weeks of the first immunization were found to be 38%, 57%, and 71%, respectively. Furthermore, in the crossantigen protection experiment, the MW2 group exhibited an RPS of 55% against the JX-01 isolate, which was significantly higher than the control group (33%). These findings suggest that an inactivated vaccine comprising an appropriate antigen isolate, when administered with a white oil adjuvant as a booster, can provide effective protection in grass carp.